Perancangan Wadah Perebusan Bakso Ikan Dengan Daya 1000 W - Lehet Rikardo Pandiangan; Romy Romy; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The development of a country coupled by the economic growth of its people, the example of a small economy is small and medium enterprises. The development of small and medium enterprises needs to be considered in line with economic growth. One of the small and medium business units in Riau is the fish meatballs processing. In the process of fish meatballs boiling have a convection heat transfer process between water and fish meatballs and conducting in a sphere of meatballs. The purpose of this research was to design the vessel of boiling fish braid container with 1000 W power capacity with automatic temperature control system. Based on the results of the study produced dimension 78 × 20 × 25 cm thickness of 1.4 mm plate and stiffeners. The result of the test result is 2.5 hours and is actually 1 hour 20 minutes. The boiling time of meatballs with size 3.1 cm is 15 minutes theoretically and 4.6 minutes onaverage from test result. The total mass of processed meatballs is 3.12 kg with total wheat balls of 163 grains.Safety factor that obtained by using software ANSYS Workbench V15.0 is 1.6.Keywords: design boiling vessel, heat transfer conduction transient, safety factor.